2013
DOI: 10.1007/s00411-013-0506-5
|View full text |Cite
|
Sign up to set email alerts
|

Absence of DNA damage after 60-Hz electromagnetic field exposure combined with ionizing radiation, hydrogen peroxide, or c-Myc overexpression

Abstract: The principal objective of this study was to assess the DNA damage in a normal cell line system after exposure to 60 Hz of extremely low frequency magnetic field (ELF-MF) and particularly in combination with various external factors, via comet assays. NIH3T3 mouse fibroblast cells, WI-38 human lung fibroblast cells, L132 human lung epithelial cells, and MCF10A human mammary gland epithelial cells were exposed for 4 or 16 h to a 60-Hz, 1 mT uniform magnetic field in the presence or absence of ionizing radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Similar to their earlier published data (Jin et al, 2012(Jin et al, , 2014, 1 mT ELF-MF in combination with 1 Gy X-rays, or H 2 O 2 or c-Myc activation did not potentiate the formation of γ-H2AX foci (Yoon et al, 2014). However, when the field strength was increased to 2 mT over the same duration (6 hours), a combination of ELF-MF and ionising radiation was capable of inducing γ-H2AX, yet both H 2 O 2 and cMyc remained incapable of this.…”
Section: Combined Elf and Carcinogen Exposuresupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to their earlier published data (Jin et al, 2012(Jin et al, , 2014, 1 mT ELF-MF in combination with 1 Gy X-rays, or H 2 O 2 or c-Myc activation did not potentiate the formation of γ-H2AX foci (Yoon et al, 2014). However, when the field strength was increased to 2 mT over the same duration (6 hours), a combination of ELF-MF and ionising radiation was capable of inducing γ-H2AX, yet both H 2 O 2 and cMyc remained incapable of this.…”
Section: Combined Elf and Carcinogen Exposuresupporting
confidence: 91%
“…Similarly, a recent series of studies performed by the same laboratory demonstrated that 4 or 16 hour exposure to 60 Hz, 1 mT ELF-MF in combination with ionising radiation (1 Gy X-rays) or H 2 O 2 or cellular myelocytomatosis oncogene (c-Myc) activation did not have either an enhancing or synergistic effect on MN formation (Jin et al, 2012) or primary DNA damage (Jin et al, 2014). However, more recently the authors re-analysed the effects of ELF-MF exposure on DNA damage response in combination with the same mutagens through the formation of γ-H2AX…”
Section: Combined Elf and Carcinogen Exposurementioning
confidence: 85%
“…Our previous study showed that exposure to a 1-mT ELF-MF for a maximum of 24 hours did not show any increase in MN formation [12] or comet tail production in several cell lines [11]. However, when we examined γH2AX, a 2-mT ELF-MF significantly increased γH2AX [14].…”
Section: Resultsmentioning
confidence: 61%
“…Previously, we investigated the effects of ELF-MFs on DNA damage responses, such as cellular transformation [10], comet tail moments [11], micronuclei formation [12], aneuploidy formation [13], and γH2AX expression [14]. These investigations were performed using non-tumorigenic epithelial or fibroblast cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation